Photochemical machining of brass with cupric chloride etchants - Cakir, Orhan (Cranfield University, 1996)
Photochemical machining is a non-conventional machining process which employs photoresist and chemical etching techniques. Brass which contains 60-80% copper and 20-40%- zinc, is the most commonly etched copper alloy in the UK. It is used to produce precision parts as well as decorative items. In this study, the most widely üsed''brass (BS CZ108, ISO CuZn37) is etched with cupric chloride. The effects of etchant concentration, temperature and hydrochloric acid additions on the etch rate, undercut, etch factors and surface roughness are determined. In comparison to cupric chloride, ferric chloride and alkaline etchants were examined. As an extension to this study, the regeneration of used cupric chloride and recovery of zinc were examined. This investigation was needed because the dissolved brass in the cupric chloride affected the etch rate and surface quality of the etched brass. Therefore the etchant had to be either replaced with fresh etchant and the spent etchant disposed of, or regenerated and the dissolved metal content recovered. The regeneration/recovery process provided an economical solution to environmental considerations. Electrodialysis was used to recover zinc and regenerate cupric chloride, and the effect of various parameters (i. e. current density, temperature, catholyte solutions) were examined and a comparison of costs between electrodialysis and chlorine regeneration was undertaken. It was noticed that the electrodialysis produced etchant and catholyte wastes. In order to eliminate any waste cupric chloride or catholyte, a further investigation using cementation was undertaken. It was noted that the cementation would successfully decrease disposal of excess solutions.